2000
DOI: 10.4049/jimmunol.165.4.2012
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Microflora and Diversification of the Rabbit Antibody Repertoire

Abstract: The rabbit establishes its primary Ab repertoire by somatically diversifying an initial repertoire that is limited by restricted V H gene segment usage during VDJ gene rearrangement. Somatic diversification occurs in gut-associated lymphoid tissue (GALT), and by about 1-2 mo of age nearly all Ig VDJ genes are somatically diversified. In other species that are known to establish their primary Ab repertoire by somatic diversification, such as chicken, sheep, and cattle, diversification appears to be developmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
72
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(79 citation statements)
references
References 52 publications
3
72
0
1
Order By: Relevance
“…Rothkötter et al (1994) found, in germ free pigs, that the maturity of the immune system at 45-d was similar to that of normal 5-d old pigs, concluding that the stimulation of bacterial flora, as well as the presence of food antigens, is necessary for a normal development of the GALT. A number of reviews, both in rabbit (Knight and Winstead, 1997;Lanning et al, 2000) and in humans (Kelly et al, 2005), indicate that the presence of saprophyte flora and, possibly of some specific genera, can be crucial for the development of the primary repertoire.…”
Section: The Development Of the Immune Systemmentioning
confidence: 99%
“…Rothkötter et al (1994) found, in germ free pigs, that the maturity of the immune system at 45-d was similar to that of normal 5-d old pigs, concluding that the stimulation of bacterial flora, as well as the presence of food antigens, is necessary for a normal development of the GALT. A number of reviews, both in rabbit (Knight and Winstead, 1997;Lanning et al, 2000) and in humans (Kelly et al, 2005), indicate that the presence of saprophyte flora and, possibly of some specific genera, can be crucial for the development of the primary repertoire.…”
Section: The Development Of the Immune Systemmentioning
confidence: 99%
“…After birth, B cells with rearranged genes migrate into gut-associated lymphoid tissue such as the appendix. Gut microflora are required for B cells to proliferate and develop in appendix follicles (3). At Ϸ3 wk of age, diversification of rearranged gene sequences by GC and SHM starts within the appendix-follicle microenvironment (2).…”
mentioning
confidence: 99%
“…It has even been shown in rabbits with ligated cecal appendix at birth (not contact with the intestinal contents) that the diversification of VDJ genes almost disappeared at 12 weeks old. The genesis of this primary repertoire would be dependent on exogenous factors (Lanning et al 2000). The good performance of the batch containing soya bean oil would be linked to the feed composition of this batch (mainly fatty acid profile of soya bean oil).…”
Section: Discussionmentioning
confidence: 99%
“…The symbiotic microflora of the digestive tract of the rabbit ensures microbial digestion and is also implicated in the digestive health of its host. It provides a protection against potentially pathogenic micro-organisms, stimulates the host immunity and diversification of the repertoire of antibodies (Lanning et al 2000;Guarner and Malagelada 2003). However, the low-growth rates observed at the first week after weaning for the two batches of rabbits are linked to the stress of weaning and the increase ingested solid compared with milk.…”
Section: Discussionmentioning
confidence: 99%